If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(k + -1) = 8 + (1 + k) Reorder the terms: -2(-1 + k) = 8 + (1 + k) (-1 * -2 + k * -2) = 8 + (1 + k) (2 + -2k) = 8 + (1 + k) Remove parenthesis around (1 + k) 2 + -2k = 8 + 1 + k Combine like terms: 8 + 1 = 9 2 + -2k = 9 + k Solving 2 + -2k = 9 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. 2 + -2k + -1k = 9 + k + -1k Combine like terms: -2k + -1k = -3k 2 + -3k = 9 + k + -1k Combine like terms: k + -1k = 0 2 + -3k = 9 + 0 2 + -3k = 9 Add '-2' to each side of the equation. 2 + -2 + -3k = 9 + -2 Combine like terms: 2 + -2 = 0 0 + -3k = 9 + -2 -3k = 9 + -2 Combine like terms: 9 + -2 = 7 -3k = 7 Divide each side by '-3'. k = -2.333333333 Simplifying k = -2.333333333
| -7/-5 | | 126=0.05x+26 | | ((9y^2)4x)12xy= | | 126.00=0.05x+26 | | 3/8+2/3 | | 5x+10y=7 | | 7y=18x+5(3+2) | | 123+889= | | -12=(5+x)^2/-3 | | 9x+224=4x+129 | | 2(b-3)-3b-7= | | x+4(x+5)=50 | | 3(4p-5)-2(p+1)=4-(p-5) | | ln(3xy)=0 | | 5y=-1.9 | | -22+x=8*x | | 8-2(b+1)=12-3b | | c^2-13c+36=0 | | x-5x=2 | | 0=t(t+2) | | (s+35)(s-40)=0 | | -22+x=8x | | a+8/3-21=-9 | | -20+-15x= | | 8-2b-2=12-3b | | x^2+3x+5=8 | | 7p-2-(3p+4)= | | 6(w+1)=-3(4w-4)+6w | | x^2-21x+294=0 | | 12a^2+6a/-3a | | 7x^2-38=74 | | -2(-6x+4)-x=3(x-2)-4 |